Cardiovascular Risk According to Body Mass Index in Women of Reproductive Age With Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis - Zhuang, Chenchen; Luo, Xufei; Wang, Wenjuan; Sun, Runmin; Qi, Miaomiao; Yu, Jing (Frontiers in Cardiovascular Medicine, 2022)
Background Polycystic ovary syndrome (PCOS) is a heterogeneous condition that affects women of reproductive age. The association between PCOS and cardiovascular risk according to body mass index (BMI) categories is unclear. Objective We evaluated the association between cardiovascular risk according to BMI categories and PCOS in women of reproductive age. Methods A literature search was conducted in the EMBASE, MEDLINE, Cochrane Library, and PubMed databases from their inception to 9 September, 2021. Observational cross-sectional, retrospective, and prospective controlled studies were included. The main analyses examined the relationship between cardiovascular risks (i.e., blood pressure and lipid levels) and BMI in women of reproductive age with PCOS. Results Thirty-eight studies, with a total of 6,078 subjects, were included in this metaanalysis. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were higher in women of reproductive age with PCOS. Lower high-density lipoprotein (HDL)-cholesterol [SMD (95% CI): −0.21 (−0.35, −0.08), p = 0.002], higher triglycerides [SMD (95% CI): 0.38 (0.29, 0.48), p < 0.001], higher low-density lipoprotein (LDL)-cholesterol [SMD (95% CI): 0.29 (0.20, 0.39), p < 0.001], higher nonHDL-cholesterol [SMD (95% CI): 0.42 (0.31, 0.52), p < 0.001] and waist-to-hip ratio (WHR) [MD (95% CI): 0.03 (0.02, 0.04), p < 0.001] were seen in women of reproductive age with PCOS. In addition, the subgroup analysis revealed that systolic BP and HDL-cholesterol increased at BMI < 25 kg/m2 and BMI 25–30 kg/m2. Diastolic BP increased at BMI 25–30 kg/m2. Triglycerides, LDL-cholesterol, nonHDL-cholesterol, and WHR increased in all BMI categories. Conclusions PCOS is associated with cardiovascular risk. Lipid levels and BP increased in women of reproductive age with PCOS, regardless of BMI. Systematic Review Registration Open Science Framework (10.17605/OSF.IO/92NBY).